2015
DOI: 10.1107/s1399004715006239
|View full text |Cite
|
Sign up to set email alerts
|

Two crystal structures of the FK506-binding domain ofPlasmodium falciparumFKBP35 in complex with rapamycin at high resolution

Abstract: Antimalarial chemotherapy continues to be challenging in view of the emergence of drug resistance, especially artemisinin resistance in Southeast Asia. It is critical that novel antimalarial drugs are identified that inhibit new targets with unexplored mechanisms of action. It has been demonstrated that the immunosuppressive drug rapamycin, which is currently in clinical use to prevent organ-transplant rejection, has antimalarial effects. The Plasmodium falciparum target protein is PfFKBP35, a unique immunophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…PfFKBP35 and its Plasmodium vivax homologue PvFKBP35 have received attention as potential antimalarial drug targets, with reports of ligands with potent antimalarial activity (Monaghan et al 2005; Harikishore et al 2013 a , b ) and atomic-level structures in complex with ligands (Kotaka et al 2008; Alag et al 2009; Bianchin et al 2015). Our understanding of the function of the protein in the parasite has however lagged behind.…”
Section: Discussionmentioning
confidence: 99%
“…PfFKBP35 and its Plasmodium vivax homologue PvFKBP35 have received attention as potential antimalarial drug targets, with reports of ligands with potent antimalarial activity (Monaghan et al 2005; Harikishore et al 2013 a , b ) and atomic-level structures in complex with ligands (Kotaka et al 2008; Alag et al 2009; Bianchin et al 2015). Our understanding of the function of the protein in the parasite has however lagged behind.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we turned to SLF as a starting point . As there are no structures of SLF -bound FKBP35 we used the structure of the related compound SLFb bound to human FKBP51­(PDB 4DRK) aligned with rapamycin-bound Pf FKBP35 (PDB 4QT2) as the basis for docking. We noted two groups proximal to C106: the aryl ring of the benzylic ester (for Series 1) and the tert -pentyl group adjacent to the ketoamide (for Series 2, Figure a), and compounds from both series were modeled (Table S2).…”
mentioning
confidence: 97%
“…The crystal structures showed that this is a reactive cysteine and being a unique residue of the Plasmodium FKBPs, it was proposed to be an attractive site for designing covalent inhibitors which can enhance the specificity of Plasmodium FKBP35 (Kotaka et al, 2008). Toward this end, the rapamycin-bound PfFKBD35 was determined in the oxidized and reduced forms (Bianchin et al, 2015). Monomeric units were captured in the crystal.…”
Section: Plasmodium Fkbpsmentioning
confidence: 99%